Prevalence of Dermatoses in Rural Paediatric Population (Community Based Medical Journal, 2013)
The spectra of the prevalence of skin diseases vary worldwide and from country to country. Therefore the information about the local prevalence of diseases is very important in helping the development of appropriate health improvement policies for promotion of better management. To document the types of skin disorders prevalent among rural children attending the Community Based Medical College Hospital out patient department, Mymensigh, a defined population based study was undertaken. The medical register from the Hospital was used to obtain information on pattern and outcome of skin diseases seen from January 2010 to December 2011. The frequency of pediatric dermatoses and their distribution patterns were studied. The results revealed that out of the 9279 Patients attending Dermatology out patient department of Community Based Medical College Hospital, 1753 (18.89%) Children were identified with involvement of skin diseases. Age range related to disease was found between one day old to 14 years. The most frequent skin condition was exposure to fungal diseases which was 25.67% followed by scabies 24.10% and eczema 20.25%. Infectious skin diseases represent considerably a high percentage of skin disorders encountered in pediatric population. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14175 Community Based Medical Journal Vol.2(1) 2013 9-14